ANALISIS KOMPARATIF KINERJA BANK SYARIAH DAN BANK PEMERINTAH KONVENSIONAL DI INDONESIA - Maya Puspita Sari (Department of Development Economics, Universitas Sriwijaya, 2009)
The objectives of this research is to analysis performance of sharia banks and state owned banks conventional in Indonesia. The term of financial performance in this research is liquidity, rentability and solvability ratio. The data that used in this research is secondary data, from Maret 2003 until December 2008. This study with analysis method is statistic non-parametric, both of test is Mann Whitney U and Kolmogorov Semirnov test. Research finding has shown that during period of years 2000-2008 condition performance of sharia banks and state owned banks conventional was different. Seeing from liquidity ratio, FDR and NPF of sharia banks better than LDR and NPL of state owned banks. Seeing from rentability ratio, ROA of state owned banks better than sharia banks. And sheeing from solvability ratio, CAR of sharia banks and state owned banks was same. Key words : Financial Performance of Banks, Sharia Banks and State Owned Banks.